Prinsip-prinsip Misi dari Teks Amanat Agung bagi Pelaksanaan Misi Gereja Masa Kini - Listari Listari; Yonatan Alex Arifianto (Jurnal Teologi Gracia Deo, 2020)
The missionary fulfillment of the Great Commission as applied to churches today. Mission shares the same principle in the Great Commission, which is to bring souls to salvation. In the text of the Great Commission, there are three important parts, namely salvation, development, and assignment. This great commission has been applied in various churches today, but the principles of the mission itself have not been fully understood by church members. By using descriptive qualitative methods, the writer can define the Great Commission and its objectives, then describe the principles of mission in the Great Commission in the study of Matthew 28: 19-20 and apply the mission in everyday life. A mission that has an agenda and objectives and mission principles from the text of the Great Commission, understands carefully the theological study of the Great Commission and knows the mission of God in the life of every believer, recognizes the mandate in the person and fulfills it. And the last, most important thing is how the church recognizes the problems in mission and strives to be a mission church that relies on God and is able to get through every challenge that exists in implementing its evangelistic mandate. Abstrak Pelaksanaan misi dari Amanat Agung yang diterapkan pada gereja-gereja masa kini. Misi memiliki prinsip yang sama dalam Amanat Agung, yaitu untuk membawa jiwa-jiwa kepada keselamatan. Dalam teks Amanat Agung terdapat tiga bagian penting, yaitu penyelamatan, pengembangan dan penugasan. Amanat Agung ini telah diterapkan di dalam berbagai gereja saat ini, hanya saja prinsip dari misi itu sendiri belum dipahami secara menyeluruh oleh anggota gereja. Dengan melalui metode kualitatif deskritif, penulis dapat mendeskritifkan Amanat Agung dan tujuannya, lalu menjabarkan prinsip misi Amanat Agung dalam kajian Matius 28: 19- 20 dan mengaplikasikan misi dalam kehidupan sehari-hari. Misi yang memiliki agenda tujuan dan prinsip- Prinsip misi dari teks Amanat Agung, memahami dengan seksama kajian teologis Amanat Agung serta mengenal misi Allah di dalam kehidupan setiap orang percaya, mengenal amanat dalam diri pribadi dan menunaikannya. Dan yang terakhir yang paling penting adalah bagaimana gereja mengenal masalah-masalah dalam misi serta berusaha menjadi gereja yang bermisi dengan bersandar Tuhan dan mampu melewati setiap tantangan yang ada dalam menerapkan mandat penginjilan.